Experiences of student nurses regarding the bursary system in KwaZulu-Natal province, South Africa - Eve Jacobs; Belinda Scrooby; Antoinette du Preez (AOSIS, 2019)
Background: During 2010, the South African nursing education system was restructured, changing student nurses from having supernumerary status to being bursary holders. Changes with the introduction of this new bursary system included institutional factors and benefits that could be removed from the students, potentially hampering students' sense of belonging. Aim: This study aimed to describe the experiences of students receiving bursaries in KwaZulu-Natal (KZN) province and to make recommendations for improving the system to bursary providers, educational institutions and practical settings based on these students' experiences of the bursary system. Setting: The experiences of student nurses regarding the bursary system are described within a specified setting comprising two nursing campuses in KZN. Method: A qualitative study design was used and seven focus group interviews were conducted with purposively selected participants, representing the target population of first-, second- and third-year male and female nursing students registered for the Diploma in Nursing (General, Psychiatric, Community) and Midwifery. Results: Two main themes and eight subthemes were identified. The findings indicated that some of the bursary system's experiences were negative as opposed to students having supernumerary status. These experiences had negative socio-economic, psychological, clinical, academic and family impacts. Many concerns related to staff members' attitudes, shortages of nurses and service demands during students' clinical practice assignments. Conclusions: The bursary system was not viewed as being beneficial to students as they did not receive all the benefits from being bursary holders. Support in clinical and academic areas was lacking as they were considered to be employees during their clinical assignments. There is an urgent need to review the bursary system.